OPPORTUNITIES TO USE ARTIFICIAL INTELLIGENCE IN IMPROVING RAILWAY TRANSPORT INFRASTRUCTURE AND INCREASING LOGISTICS EFFICIENCY (Marketing Journal, 2025)
The article examines the application potential of artificial intelligence technologies in railway transport infrastructure. The focus is on improving diagnostic and maintenance efficiency, modeling freight flows, utilizing Digital Twins, and optimizing hig h-speed train management. The analysis of scientific sources indicates that AI technologies play a crucial role in enhancing safety, reducing operational costs, and effectively organizing logistics processes. The proposed approaches can contribute to the s ustainable development of the transport system.
Keywords: railway transport; artificial intelligence (AI); diagnostics; modeling; Digital Twin; logistics; efficiency; safety. 204